2005
DOI: 10.1126/science.1116495
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Zinc Oxide Nanobelts into Superlattice-Structured Nanohelices

Abstract: A previously unknown rigid helical structure of zinc oxide consisting of a superlattice-structured nanobelt was formed spontaneously in a vapor-solid growth process. Starting from a single-crystal stiff nanoribbon dominated by the c-plane polar surfaces, an abrupt structural transformation into the superlattice-structured nanobelt led to the formation of a uniform nanohelix due to a rigid lattice rotation or twisting. The nanohelix was made of two types of alternating and periodically distributed long crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
466
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 844 publications
(476 citation statements)
references
References 13 publications
7
466
0
3
Order By: Relevance
“…In addition, more complicated structures such as nanobelts 7,8 , nanohelices 9 , and others [10][11][12] have been synthesized. Unfortunately, the ZnO band gap (3.4 eV) is too large for use in efficient photovoltaic devices.…”
mentioning
confidence: 99%
“…In addition, more complicated structures such as nanobelts 7,8 , nanohelices 9 , and others [10][11][12] have been synthesized. Unfortunately, the ZnO band gap (3.4 eV) is too large for use in efficient photovoltaic devices.…”
mentioning
confidence: 99%
“…5 The reduction in the area of polar surfaces causes a structural transformation of a single-crystal ZnO nanobelt into a superlattice-structured, partial-polar surface dominated nanobelt, which eventually forms a rigid nanohelix. 6 Besides the nanorings observed for wurtzite AlN due to polar surfaces, 7 no report has been found on the formation of single-crystalline rings/springs/ spirals for a material that has a structure different from wurtzite.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] Moreover, ZnO nanostructures show a variety of different morphological configurations that include nanowires, 21 nanobelts, 22 nanosprings, 23 nanorings, 24 nanobows, 25 and nanohelices. 26 Among these nanostructures, nanowires exhibit remarkably enhanced piezoelectric responses. According to previous experimental results, 27 the piezoelectric coefficient of the ZnO nanowire with a diameter of 230 nm is as high as 1200 pm V À1 which is two orders of magnitude larger than that of the bulk ZnO (9.93 pm V À1 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of first-principles calculations, Agrawal et al 28 recently showed that the observed giant piezoelectric responses of ZnO nanowires mainly stem from the size effects. In spite of extensive experimental [21][22][23][24][25][26][27][28][29] and theoretical 16,17,20,[30][31][32][33] studies on its piezoelectric properties and technological applications, however, little progress has been made in our fundamental understanding of the microscopic origin of piezoelectricity in the wurtzite ZnO.…”
Section: Introductionmentioning
confidence: 99%